LEAF HAIRINESS IN POTATO Solanum tuberosum: MORPHOLOGY, FUNCTION AND METHODS OF ANALYSIS - A. V. Doroshkov; D. A. Afonnikov (Вавиловский журнал генетики и селекции)
Pubescence is one of the important biotic factors in plants related to protection from stressful environmental factors. In potato, the interest in the study of pubescence is associated primarily with the fact that it plays a significant role in the protection of plants from insect pests. The review focuses on the functional role and genetic control of leaf pubescence in potato. The review describes morphological features of pubescence of potatoes, which consists of simple and glandular trichomes of several types. The ratio of trichomes of different types in potato species potato is diverse, especially for wild species. Therefore, the pubescence may serve as a classifying trait. The role of trichomes as “factories” of secondary metabolites of potatoes, among which are the esters of sucrose and terpene derivatives that serve as insect repellents. Trichomes also synthesize polyphenol oxidases, which lead to the biosynthesis of compounds which are harmful to the insects. The review presents information about the currently known genes responsible for pubescence. These are genes involved in the formation of a complex of MYB-bHLH-WD40, which controls the differentiation and development of trichomes in plants. The proteins of this complex in potatoes are primarily studied in connection with the regulation of the biosynthesis of anthocyanins. The fundamental basis for identification of genes controlling pubescence in potato is currently sequence data from complete genome sequencing. By analysis of homology with the genes of model organisms, it allows candidate genes that control important traits in potato to be identified. Work in this direction is already underway, but at the initial stage. In the final section, the review describes the methods ofphenotyping trichomes, based on the visual analysis of microscopic images (obtained both with optical and electron microscopes). The urgency of developing new high-performance approaches to the study of the morphology of the trait in potatoes has been demonstrated.